A rapid review of adolescent engagement in massive open online courses (MOOCS) in health and education: Content, engagement strategies and evaluation methods - Putu Novi Arfirsta Dharmayani; Allyson R. Todd; Jennifer Dam; Josephine Y. Chau; Sara Wardak; Katrina E. Champion; Seema Mihrshahi; Stephanie R. Partridge (Health Literacy and Communication Open)
Objectives Rapid digital technology development has greatly expanded the access to and availability of distance learning courses, including the proliferation of massive open online courses (MOOCs). Despite their growing popularity, there is a notable scarcity of research focusing on MOOCs for adolescents as audiences or users. This rapid review aimed to explore the utilisation of MOOCs, engagement strategies, and evaluation methods for adolescents aged 10–19 years in general, and particularly in health-related courses.Study design The design of this study is a rapid review.Methods Five electronic databases yielded 2685 studies, which were then dual-screened against the eligibility criteria. A narrative synthesis method was used to summarise findings based on the following themes: topics covered in MOOCs, engagement strategies and MOOC content, and evaluation methods.Results Twenty-three studies were included in this review, with six health-related topics. Course resources were classified into four categories: reading and visual materials, videos, assessments, and other learning activities. Engagement levels varied across the studies, with greater adolescent engagement in health-related MOOCs. Facilitators of MOOC engagement included personal interest and a sense of achievement, whereas barriers included using technical language, lack of visual and graphic content, and lack of interaction. Evaluation methods predominantly used multiple sources, with self-reported surveys being the most common. Emotional and cognitive engagement were frequently reported in learning engagement domains in MOOCs.Discussion Overall, this review highlights the importance of active engagement of adolescents using collaborative digital tools and advocates for adopting a mixed-methods approach to evaluate MOOCs to achieve optimal outcomes.